Oliver's great big universe - Cham, Jorge (New York : Amulet Books, 2023)
An aspiring astrophysicist, 11-year-old Oliver takes on the whole universe, explaining everything he learns, while starting his first year of middle school with new friends, new classes, new everything--where the only thing that still makes sense is science.
Kirkus Starred, August 2023
Includes bibliographical references and index.
5.6
3-6
740L
Keywords: Middle school students -- Juvenile fiction; Middle schools -- Juvenile fiction; Astronomy -- Juvenile fiction; Astrophysics -- Juvenile fiction; Humorous stories; Middle school students -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Astronomy -- Fiction; Astrophysics -- Fiction; School fiction; Humorous fiction